You are on page 1of 8

Alain J.

Brizard Saint Michael's College

Lagrangian Mechanics
1 Principle of Least Action

The conguration of a mechanical system evolving in an n-dimensional space, with coordinates x = (x1 ; x2 ; :::; xn), may be described in terms of generalized coordinates q = (q1 ; q2; :::; q k ) in a k-dimensional conguration space, with k < n. The Principle of Least Action (also known as Hamilton's principle) is expressed in terms of a function L(q; q; t) known as the Lagrangian, which appears in the action integral _ A[q] =
Z tf
ti

_ L(q; q; t) dt;

(1)

where the action integral is a functional of the vector function q(t), which provides a path from the initial point q i = q(ti) to the nal point qf = q(tf ). The variational principle
" !# Z tf d @L d @L j 0 = A[q] = A[q + q] = q dt; d ti @ qj dt @ qj _ =0

where the variation q is assumed to vanish at the integration boundaries (q i = 0 = qf ), yields the Euler-Lagrange equation for the generalized coordinate qj (j = 1; :::; k) d dt

@L @ qj _

@L ; @ qj

(2)

The Lagrangian also satises the second Euler equation d @L L qj _ dt @q j _


!

@L ; @t

(3)

and thus for time-independent Lagrangian systems (@L=@t = 0) we nd that L q j @L=@ qj _ _ is a conserved quantity whose interpretation will be discussed shortly. _ The form of the Lagrangian function L(r; r; t) is dictated by our requirement that Newton's Second Law m = rU(r; t) describing the motion of a particle of mass m in a r nonuniform (possibly time-dependent) potential U(r; t) be written in the Euler-Lagrange form (2). One easily obtains the form L(r; r; t) = _ m 2 j_ j U (r; t); r 2 1 (4)

which is simply the kinetic energy of the particle minus its potential energy. For a timeindependent Lagrangian (@L=@t = 0), we also nd that the energy function r _ m 2 @L L = j_ + U (r) = E; rj @r _ 2

is a constant of the motion. Hence, for a simple mechanical system, the Lagrangian function is obtained by computing the kinetic energy of the system and its potential energy and then construct Eq. (4).

Examples

The construction of a Lagrangian function for a system of N particles proceeds in three steps as follows. Step I. Dene k generalized coordinates fq1 (t); :::; q k(t)g that represent the instantaneous conguration of the system of N particles. Step II. Construct the position vector ra (q; t) and its associated velocity va (q; q; t) = _ for each particle (a = 1; :::; N). Step III. Construct the kinetic energy _ K(q; q; t) = 1 X _ ma jv a (q; q; t)j 2 2 a
k X j @ra @r a + q _ @t @q j j=1

and the potential energy U (q; t) for the system and combine them to obtain the Lagrangian L(q; q; t) = K (q; q; t) U(q; t); _ _ from which the Euler-Lagrange equations (2) are derived.

2.1

Example I: Pendulum

Consider a pendulum composed of an object of mass m and a massless string of constant length ` in a constant gravitational eld with acceleration g.

Although the motion of the pendulum is two-dimensional, a single generalized coordinate is needed to describe the conguration of the pendulum: the angle measured from the negative y-axis (see Figure above). Here, the position of the object is given as x() = ` sin and y() = ` cos ; with associated velocity components _ _ _ _ x(; ) = ` cos and y(; ) = ` sin : _ _ Hence, the kinetic energy of the pendulum is K = m 2 _2 ` ; 2

and choosing the zero potential energy point when = 0 (see Figure above), the gravitational potential energy is U = mg` (1 cos ): The Lagrangian L = K U is, therefore, written as m 2 _2 _ L(; ) = ` mg` (1 cos ); 2 and the Euler-Lagrange equation for is @L d 2 _ _ = m` ! dt @
!

@L = m`2 _ @ @L = mg` sin @

or

g + sin = 0 `

2.2

Example II: Bead on a Rotating Hoop

Consider a bead of mass m sliding freely on a hoop of radius R rotating with angular velocity !0 in a constant gravitational eld with acceleration g.

Here, since the bead of the rotating hoop moves on the surface of a sphere of radius R, we use the generalized coordinates given by the two angles (measured from the negative z-axis) and ' (measured from the positive x-axis), where ' = !0 . The position of the bead _ is given as x(; t) = R sin cos('0 + !0t); y(; t) = R sin sin(' 0 + !0t); z(; t) = R cos ; where '(t) = '0 + !0 t and its associated velocity components are _ _ x(; ; t) = R cos cos ' !0 sin sin ' ; _ _ _ y(; ; t) = R cos sin ' + !0 sin cos ' ; _ _ _ z(; ; t) = R sin ; _ so that the kinetic energy of the bead is
m m R2 _ 2 2 _ K(; ) = jvj 2 = + !0 sin2 : 2 2 The gravitational potential energy is

U() = mgR (1 cos ); where we chose the zero potential energy point at = 0 (see Figure above). The Lagrangian L = K U is, therefore, written as
m R2 _ 2 _ L(; ) = + !2 sin2 mgR (1 cos ); 0 2

and the Euler-Lagrange equation for is @L d _ = mR2 ! _ dt @

@L = mR2 _ @ @L = mgR sin @ 2 + mR2 !0 cos sin

or

+ sin g ! 2 cos = 0 0 R

2.3

Example III: Rotating Pendulum

Consider a pendulum of mass m and length b attached to the edge of a disk of radius a rotating at angular velocity ! in a constant gravitational eld with acceleration g.

Placing the origin at the center of the disk, the coordinates of the pendulum mass are x = a sin !t + b cos y = a cos !t + b sin so that the velocity components are _ x = a! cos !t b sin _ _ y = a! sin !t + b cos _ and the squared velocity is _ _ v2 = a2!2 + b2 2 + 2 ab ! sin( !t): Setting the zero potential energy at x = 0, the gravitational potential energy is U = mg x = mga sin !t mgb cos : 5

The Lagrangian L = K U is, therefore, written as


i mh 2 2 _ _ _ L(; ; t) = a ! + b2 2 + 2 ab ! sin( !t) 2 mga sin !t + mgb cos ;

(5)

and the Euler-Lagrange equation for is @L _ = mb2 + m ab ! sin( !t) ! _ @ ! d @L _ = mb2 + m ab ! ( !) cos( !t) _ dt @ and or @L _ = m ab ! cos( !t) mg b sin @

g a + sin !2 cos( !t) = 0 b b We recover the standard equation of motion for the pendulum when a or ! vanish. Note that the terms [(m=2) a 2!2] and [ mga sin !t] in the Lagrangian (5) play no role in determining the dynamics of the system. In fact, as can easily be shown, a Lagrangian L is always dened up to an exact time derivative, i.e., the Lagrangians L and L0 = L+ df=dt, where f (q; t) is an arbitrary function, lead to the same Euler-Lagrange equations. In the present case, f (t) = [(m=2) a2! 2] t + (mga=!) cos !t and thus this term can be omitted from the Lagrangian (5) without changing the equations of motion.

2.4

Example IV: Compound Atwood Machine

Consider a compound Atwood machine composed three masses (labeled m1 , m2, and m3 ) attached by two massless ropes through two massless pulleys in a constant gravitational eld with acceleration g. The two generalized coordinates for this system (see Figure) are the distance x of mass m1 from the top of the rst pulley and the distance y of mass m2 from the top of the second pulley; here, the lengths `a and `b are constants.

The coordinates and velocities of the three masses m1 , m2, and m3 are x1 = x ! v1 = x; _ x2 = `a x + y ! v2 = y x; _ _ x3 = `a x + `b y ! v3 = x y; _ _ respectively, so that the total kinetic energy is m1 2 m2 m3 K = x + _ (y x)2 + _ _ (x + y)2 : _ _ 2 2 2 Placing the zero potential energy at the top of the rst pulley, the total gravitational potential energy, on the other hand, can be written as U = g x (m1 m2 m3 ) g y (m2 m3) ; where constant terms were omitted. The Lagrangian L = K U is, therefore, written as m1 2 m2 m3 L(x; x; y; y) = _ _ x + _ ( x y)2 + _ _ (x + y)2 _ _ 2 2 2 + g x (m1 m2 m3 ) + g y (m2 m3) : The Euler-Lagrange equation for x is @L = (m1 + m2 + m3 ) x + (m3 m2) y ! _ _ @ x ! _ d @L = (m1 + m2 + m3) x + (m3 m2 ) y dt @ x _ @L = g (m1 m2 m3 ) @x 7

while the Euler-Lagrange equation for y is @L = (m3 m2) x + (m2 + m3) y ! _ _ @y _ ! d @L = (m3 m2 ) x + (m2 + m3 ) y dt @ y _ @L = g (m2 m3) @y or (m1 + m2 + m3 ) x + (m3 m2) y = g (m1 m2 m3 ) (m3 m2) x + (m2 + m3) y = g (m2 m3)

Symmetries and Conservation Laws

The Noether theorem states that for each symmetry of the Lagrangian there corresponds a conservation law (and vice versa). When the Lagrangian L is invariant under a time translation, a space translation, or a spatial rotation, the conservation law involves energy, linear momentum, or angular momentum, respectively. When the Lagrangian is invariant under time translations, t ! t + t, the Noether theorem states that energy is conserved, dE=dt = 0, where E = dq @L L _ dt @ q

denes the energy invariant. When the Lagrangian is invariant under spatial translations or rotations, ! + , the Noether theorem states that the component p = @L @q @L = @ _ @ @ q _

of the canonical momentum p = @L=@ q is conserved, dp =dt = 0. Note that if is a _ linear spatial coordinate, p denotes a component of the linear momentum while if is an angular spatial coordinate, p = L denotes a component of the angular momentum (with denoting the axis of symmetry about which is measured).